Ovarian peroxidase and sialic acid activities during the reproductive cycle of Heteropneustes fossilis (Bloch) - Ghosh, Subho; Gupta, Santasri Sen; Ghosh, Ashok (Indian Journal of Fisheries, 2011)
Peroxidase enzyme and sialic acid are spectrophotometrically estimated fromthe ovaries of the Indian catfish (Heteropneustes fossilis) during the annualovarian cycle. Three phases of the reproductive cycle identified are, last partof pre-spawning, spawning and first part of post-spawning. It becomes evidentthat peroxidase is the "marker enzyme" during the spawning period ofH. fossilis